Narrating Conversion in Augustine’s Notes on Job - Nataliya D. Pratsovyta (Religions)
This article explores the themes of repentance and conversion in Augustine’s Notes on Job. Despite its fragmentary and often improvisational character, Augustine’s theological vision in the Notes presents Job as an exemplum of ongoing conversion. Though not portrayed as a sinner, Job undergoes spiritual transformation, embodying the human need for continual repentance and deeper understanding of God. This treatment aligns with Augustine’s depiction of other biblical figures, such as St. Paul and the Prodigal Son, whose stories serve as models of conversion. By closely examining the rhetorical and theological function of Job in the Notes, the article suggests that Augustine’s portrayal was meant to guide readers on the path toward salvation. In doing so, it contributes to a broader understanding of how Augustine constructs conversion narratives within his biblical commentaries.